Stress and Coping among Nursing Students (Journal of Nobel Medical College, 2024)
Background: Student at the university level experience high level of stress, related to worry about successes, availability of time and engagement in patient care. Coping mechanisms are essential when trying to deal with the stress and anxiety that nursing students face on a daily basis. The objectives of this study was to find out the level of stress and coping among nursing students and to find out the association between level of stress and coping with selected socio demographic variables.Materials and Methods: A descriptive cross sectional research design was adopted for the study. Non probability total enumerative sampling technique was used in the study. A structured questionnaire consisting of 5 points Likert scale was used for assessing the stress whereas Brief cope scale was used for assessing the coping among nursing students. Data was analyzed by using descriptive and inferential statistics.Results: The result depicts that out 107 respondents, more than two third (68.2%) of the respondents had high level of stress whereas more than half (60.7%) of the respondents had average coping. There was statically significant association between the age of the respondents with the level of stress whereas there was no statically significant association between coping with the socio demographic characteristics of respondents.Conclusion: The study concluded that, more than two third respondents had high level of stress with average coping. So, there is further need of nursing educators to provide stress management technique educational program to nursing students.